MATHEMATICAL COMPUTER-BASED MODELS OF RAILWAY TRACTION SUBSTATIONS COMPUTER NETWORKS INFORMATION SECURITY - Стасюк, Олександр Іонович; Грищук, Руслан Валентинович; Гончарова, Лідія Леонідівна (Ukrainian Information Security Research Journal, 2015)
Based on the analysis of the complex security issues oflocal area networks railway traction substations information resources shown that generally accepted in the world is thedirection of intellectualization of computer networks, as abasis for improving the safety of railway transport and the development of advanced energy-saving technologies ofelectricity consumption. Formed logical structure of a localarea network operational management of power supply inthe form of a graph that displays the topological characteristics of traction substation, and also developed amathematical model of it in the form of systems ofdifferential equations. Applied modern methods of differential transformations to determine the probabilitiesof the states of nodes of the graph representing the localarea network of traction substation. Formulated criteria forinformation security and provided strategies for ensuringthe principle of minmax. The necessary and sufficient conditions for an extremum, which opens up the possibility of finding the optimal search strategy. Showed the necessary and sufficient conditions for an extremum, which opens up the possibility of finding the optimal searchstrategy.